EVALUASI PRODUKSI DAN PERSEDIAAN PADA PRODUK PIPA DI CV.XYZ - Putri Ma'arif, Dinda Eka; Abdulrahim, Muslimin (J-ENSITEC, 2024)
CV. XYZ is a distributor of building materials but focuses on PVC pipe products under the Target brand. CV. XYZ was founded in 2013. At CV. XYZ is very necessary for inventory scheduling which needs to be carried out by CV. XYZ in order to always meet consumer demand. The author suggests inventory calculations and scheduling to meet consumer demand using the Distribution Requirement Planning (DRP) method. In the DRP method there are several stages of data needed, namely demand data, inventory, lead time, holding cost data. Data processing in this DRP method is demand forecasting, determining Lead Time, determining lot size, calculating safety stock, and creating DRP tables. In the calculation results, results were obtained for distribution costs for 5 pipe products which initially had excess stock and could not meet demand. For Target Pipe AW 1.0 x 4m products savings of 33%, Target Pipe AW 2 ½ x 4m savings of 67%, Target Pipe C 5/8 x 4m savings of 67%, Target Pipe D 1 ½ savings of 50%, Target Pipe D 6.0 x 4m savings of 67%.